Middle Stone Age mineral pigment procurement at Pinnacle Point 5–6 North, Western Cape province, South Africa. (28th June 2021) - McGrath, James R.; MacDonald, Brandi L.; Stalla, David
Abstract: We report on a multi‐method sourcing study of 35 mineral pigment artefacts from the Middle Stone Age site of Pinnacle Point 5–6 North (PP5–6 N), dating from about 90–50 ka. The artefacts were analysed and compared with geological samples from seven sources using neutron activation analysis (NAA), and supplemented by data from X‐ray diffraction (XRD) and scanning electron microscopy (SEM). Our preliminary results suggest that the occupants of PP5–6 N likely used at least two local and one currently unidentified and possibly non‐local Fe oxide mineral pigment sources. The mineral pigment artefacts derived from the latter source(s) exhibited manganese (Mn) enrichment with concentrations well above those observed in all sampled source deposits in the study area, suggesting a distinctive formation process. The proportions of the Mn‐enriched mineral pigment artefacts within the PP5–6 N assemblage vary over time, but tend to occur at higher rates in the glacial Marine Isotope Stage (MIS) 4 deposits, which holds potential implications for changes in the use of sources over time, increased mobility or increased exchange during this period.